The Ecofeminism and Implementation at Indonesian Language Learning Class of the Song Lyric Seperti Rahim Ibu by Efek Rumah Kaca Band - Guci, Aldo Ferdianda (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
This research discusses the form of ecofeminism in the lyrics of songs Seperti Rahim Ibu by the band Efek Rumah Kaca and its implications for Indonesian language learning for class high school. The aim of this research is to describe the ecofeminist values ​​contained in the lyrics of the song "Seperti Rahim Ibu" by the Efek Rumah Kacaband, such as (1) the existence of an important link between (oppression) the treatment of women and nature, (2) understanding nature in this case is important for gain an adequate understanding of the oppression (treatment) of women and nature, (3) feminist theory and practice must include an ecological perspective, and (4) solving ecological problems must include a feminist perspective. As well as the implications for learning Indonesian in Class X Senior High School. The approach used in this research is a qualitative approach using content analysis methods. The data used in this research are quotations from the lyrics of the song "Seperti Rahim Ibu " by the band Efek Rumah Kaca. Data collection techniques use documentation studies or literature reviews. The lyrics of the song Seperti Rahim Ibu by the band Efek Rumah Kaca are the main data source in the research. The results of the research found nineteen song lyrics in the form of ecofeminist values ​​contained in the lyrics of the song Seperti Rahim Ibu by the Efek Rumah Kaca band. In the form of ecofeminist values ​​1) There is an important connection between (oppression) the treatment of women and nature, three quotes. 2) Understanding nature in this case is important to gain an adequate understanding of the oppression (treatment) of women and nature, five quotes. 3) Feminist theory and practice must include an ecological perspective, three quotes. And 4) Solving ecological problems must include a feminist perspective, eight quotes. The benefits of this research can be implied and used as teaching material in learning Indonesian in Senior high school.